2011
DOI: 10.1371/journal.pone.0014731
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Sirt3 Protects against Excitotoxic Injury in Mouse Cortical Neuron Culture

Abstract: BackgroundSirtuins (Sirt), a family of nicotinamide adenine nucleotide (NAD) dependent deacetylases, are implicated in energy metabolism and life span. Among the known Sirt isoforms (Sirt1-7), Sirt3 was identified as a stress responsive deacetylase recently shown to play a role in protecting cells under stress conditions. Here, we demonstrated the presence of Sirt3 in neurons, and characterized the role of Sirt3 in neuron survival under NMDA-induced excitotoxicity.Methodology/Principal FindingsTo induce excito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
131
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 71 publications
6
131
0
1
Order By: Relevance
“…While ROS are required for glucose metabolism and metastasis in triple-negative breast cancers (9), decreased SirT3 levels concomitant with high ROS levels are frequently observed in all breast cancers (8). Based on these findings, SirT3 is considered a tumor suppressor (5,8).SirT3 regulates the activity of magnesium superoxide dismutase (MnSOD), which detoxifies superoxide to hydrogen peroxide (5,7,(10)(11)(12)(13)(14). Moreover, SirT3 has been linked to augmented transcription of MnSOD and catalase, both known targets of the transcription factor FOXO3A (15).…”
mentioning
confidence: 99%
“…While ROS are required for glucose metabolism and metastasis in triple-negative breast cancers (9), decreased SirT3 levels concomitant with high ROS levels are frequently observed in all breast cancers (8). Based on these findings, SirT3 is considered a tumor suppressor (5,8).SirT3 regulates the activity of magnesium superoxide dismutase (MnSOD), which detoxifies superoxide to hydrogen peroxide (5,7,(10)(11)(12)(13)(14). Moreover, SirT3 has been linked to augmented transcription of MnSOD and catalase, both known targets of the transcription factor FOXO3A (15).…”
mentioning
confidence: 99%
“…Recent studies have indicated that neuronal SIRT3 protects cells against excitotoxicity (44). Notably, we found that mutant Htt depleted SIRT3 protein levels.…”
Section: Discussionmentioning
confidence: 47%
“…SIRT3 was important for neuron viability in a primary cell model that used NMDA to deplete NAD and induce excitotoxic injury (105). Mice with a neuron-specific deletion of Sirt6 did not die of hypoglycemia like full-body knock-outs (79).…”
Section: Brainmentioning
confidence: 99%